Craniofacial changes and symptoms of sleep-disordered breathing in healthy children - Maria Christina Thomé Pacheco; Bruna Santos Fiorott; Nathalia Silveira Finck; Maria Teresa Martins de Araújo (Dental Press Editora, 2015)
INTRODUCTION: The main cause of mouth breathing and sleep-disordered breathing (SDB) in childhood is associated with upper airway narrowing to varying degrees. OBJECTIVE: The aim of this study was to assess the prevalence of morphological and functional craniofacial changes and the main clinical symptoms of SDB in healthy children. METHODS: A cross-sectional observational study was conducted. A sample comprising 687 healthy schoolchildren, aged 7-12 years old and attending public schools, was assessed by medical history, clinical medical and dental examination, and respiratory tests. The self-perceived quality of life of mouth breathing children was obtained by a validated questionnaire. RESULTS: Out of the total sample, 520 children were nose breathers (NB) while 167 (24.3%) were mouth breathers (MB); 32.5% had severe hypertrophy of the palatine tonsils, 18% had a Mallampati score of III or IV, 26.1% had excessive overjet and 17.7% had anterior open bite malocclusion. Among the MB, 53.9% had atresic palate, 35.9% had lip incompetence, 33.5% reported sleepiness during the day, 32.2% often sneezed, 32.2% had a stuffy nose, 19.6% snored, and 9.4% reported having the feeling to stop breathing while asleep. However, the self-perception of their quality of life was considered good. CONCLUSION: High prevalence of facial changes as well as signs and symptoms of mouth breathing were found among health children, requiring early diagnosis and treatment to reduce the risk of SDB.